FIKIH MUSLIM MINORITAS DI NON-MUSLIM MAYORITAS - Miskari Miskari (Fakultas Syariah (Syari'ah Faculty ), 2015)
There is a (legal) field known as ‘Muslim Minorities Jurisprudence’ (Fiqh al-Aqlliyat al-Muslimah or Minority Fiqh) for those who live in different reality than that of muslims residing in Islamic countries. The muslim minority have decided to examine the reality of these communities and make legal decisions for them, since the problems they face as minorities are very different from those in an Islamic country. Minority Fiqh has emerged as a distinctive field of research in the wake of the post World War II establishment of sizable Muslim populations in western Europe and North America. But, the current debate on whether Muslims should devise a new understanding of Islamic law for minorities is therefore a thoroughly modern one, engaging a wide number of contemporary Muslim scholars and intellectuals. It cannot include Fiqh al-Aqaliyyat in the meaning of Fiqh as it is now commonly understood; namely, applied branches of Fiqh (Fiqh al-Furu'). It is more appropriate to include it under Fiqh in the general sense, which includes all aspects of law in thought and practice